Psychological Aspects of Androgen Insensitivity Syndrome: Two Cases Illustrating Therapeutical Challenges - Filippa Pritsini; Georgios A. Kanakis; Ioannis Kyrgios; Eleni P. Kotanidou; Eleni Litou; Konstantina Mouzaki; Aggeliki Kleisarchaki; Dimitrios G. Goulis; Assimina Galli-Tsinopoulou (Case Reports in Endocrinology)
Androgen Insensitivity Syndrome (AIS) and its heterogeneous phenotypes comprise the pieces of a challenging clinical problem. The lack of standardized guidelines results in controversies regarding the proper diagnostic and therapeutic approach, including the time and type of intervention. Due to its variable phenotype, AIS is not diagnosed at the proper age that would allow optimal psychological and medical support to the patient. Therapeutic approaches are not established, mainly due to the rarity of the disease. In addition, various social and ethical consequences may emerge. The aim of this double case report is to outline the difficulties that may rise during diagnostic, therapeutic, and psychological approach of AIS, especially concerning the handling of the relatives’ reaction.